2007
DOI: 10.1021/ja064984p
|View full text |Cite
|
Sign up to set email alerts
|

Iron(III) Complex of a Crown Ether−Porphyrin Conjugate and Reversible Binding of Superoxide to Its Iron(II) Form

Abstract: The synthesis and characterization of the Fe(III) complex of a novel crown ether-porphyrin conjugate, 52-N-(4-aza-18-crown-6)methyl-54,104,154,204-tetra-tert-butyl-56-methyl-5,10,15,20-tetraphenylporphyrin (H2Porph), as well as the corresponding hydroxo, dimeric, Fe(II), and peroxo species are reported. The crystal structure of [FeIII(Porph)Cl].H3O+.FeCl4-.C6H6.EtOH is also reported. [FeIII(Porph)(DMSO)2]+ and K[FeIII(Porph)(O22-)] are high-spin species (Mössbauer data: delta = 0.38 mm s(-1), DeltaEq = 0.83 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 44 publications
1
40
0
Order By: Relevance
“…Further characterization of the O-O and Fe-O bonding by IR, rR, and EXAFS spectroscopy supported a symmetrically bound peroxo ligand [39,41]. These data have served as benchmarks for the characterization of other model compounds (14b-d, 16) ( Figure 6), which all show similar spectroscopic features [42][43][44]. In a more recent report, compound 16 was found to be in equilibrium with an Fe(II)-O [42].…”
Section: Fe(iii)-superoxo Intermediatesmentioning
confidence: 72%
See 1 more Smart Citation
“…Further characterization of the O-O and Fe-O bonding by IR, rR, and EXAFS spectroscopy supported a symmetrically bound peroxo ligand [39,41]. These data have served as benchmarks for the characterization of other model compounds (14b-d, 16) ( Figure 6), which all show similar spectroscopic features [42][43][44]. In a more recent report, compound 16 was found to be in equilibrium with an Fe(II)-O [42].…”
Section: Fe(iii)-superoxo Intermediatesmentioning
confidence: 72%
“…These data have served as benchmarks for the characterization of other model compounds (14b-d, 16) ( Figure 6), which all show similar spectroscopic features [42][43][44]. In a more recent report, compound 16 was found to be in equilibrium with an Fe(II)-O [42]. Kinetic and equilibrium studies showed the reaction between the Fe(II) precursor and O À 2 to be fast, with the equilibrium strongly in favor of the bound species.…”
Section: Fe(iii)-superoxo Intermediatesmentioning
confidence: 98%
“…These reactions are usually very fast, even when they proceed in a stoichiometric manner in aprotic media, and for their detailed investigations usually low temperatures are needed. 4,23 Since the majority of reactions of metal complexes are significantly slowed down in ionic liquids, 24,25 this can be valuable for their kinetic/mechanistic studies, and may enable their examination under room temperature conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To pursue the above-mentioned concept of utilizing ILs as a medium for monitoring reactions between superoxide and metal centers, we have studied the reactions of highly charged Fe(P4+), Fe(P8+), and Fe(P8−) iron porphyrins ( 4 ], by using time-resolved UV/vis stopped-flow measurements, mass spectrometry, EPR, and XPS measurements. These complexes are known to be water-soluble, 36,37 and we found that they are soluble in ionic liquids as well.…”
Section: ■ Introductionmentioning
confidence: 99%
“…17 Since the first example of crown ether-appended porphyrins reported by Thanabal and Krishnan, 18 a number of porphyrins bearing crown ether moieties have been synthesized, and the complexation of the crown ether units with a variety of cations to form porphyrin dimers or donor-acceptor dyads has been studied. [19][20][21][22][23][24] We report here the synthesis and cation-induced dimerization of zinc 5,10,15,20-tetrakis[(benzo-18-crown-6)-4 0 -ylethynyl]-porphyrin (1), in which the crown ether and porphyrin ring are bridged by an ethynyl linker as shown in Figure 1. The crown ether units in 1 are more flexible for rotation than those in the porphyrin system with benzo-crown ethers appended directly at the mesopositions such as zinc 5,10,15,20-tetrakis[(benzo-18-crown-6)-4 0 -yl]porphyrin (2) 18 and zinc 5,10,15,20-tetrakis[(benzo-15-crown-5)-4 0 -yl]porphyrin (3).…”
Section: Introductionmentioning
confidence: 99%